Eriodictyol Attenuates Myocardial Ischemia-Reperfusion Injury through the Activation of JAK2 - Li, Defang; Lu, Ning; Han, Jichun; Chen, Xiaoyu; Hao, Wenjin; Xu, Wenjuan; Liu, Xiaona; Ye, Lei; Zheng, Qiusheng (Frontiers in Pharmacology, 2018)
Myocardial ischemia-reperfusion (I/R) injury remains the leading risk factor of disability and mortality worldwide. In this study, the myocardial protective effect of eriodictyol (EDT) and the underlying mechanism in an ex-vivo model of global myocardial I/R was investigated. After treatment with different concentrations of EDT, the decreased hemodynamic parameters induced by myocardial I/R injury were significantly attenuated by EDT. The elevated levels of IL-6, CRP, IL-8 and TNF-α were effectively reduced by EDT treatment. EDT also remarkably suppressed the levels of Bax and cleaved Caspase-3, and up-regulated the level of Bcl-2 in cardiac tissues from EDT-treated groups. Further studies showed that EDT could increase the levels of p-JAK2 and p-STAT3 in cardiac tissues. Meanwhile, treatment of AG490, a specific inhibitor of JAK2, abolished the protective effect of EDT on hemodynamic parameters, myocardial inflammation and myocardial cell apoptosis induced by I/R injury. These results demonstrated that EDT could protect against myocardial I/R injury through the activation of JAK2, providing a potential treatment with EDT during myocardial I/R injury.